Елементи договірних відносин роздрібної купівлі-продажу - Вусатий, Д. Ю.; Vusatyi, D. Yu. (Право і безпека. - 2014. - № 4 (55). - С. 182-186, 2014)
Розглянуто елементи договірних відносин роздрібної купівлі-продажу. Вказано, що суб’єктами таких відносин на боці продавців товарів можуть бути як фізичні особи – підприємці, так і юридичні особи, які мають право займатися бізнесом у сфері роздрібної торгівлі. Об’єктом цих відносин визначено поведінку (дії) їх сторін із приводу передачі права власності на майно – товари, що зазвичай призначаються для особистого, домашнього або іншого використання, не пов’язаного з підприємницькою діяльністю. Змістом зазначених відносин є суб’єктивні права й обов’язки як міра можливої або необхідної поведінки їх сторін у такого роду правовідносинах.

The relevance of the article due to the need to study the elements of contractual relations retail purchase and sale in accordance with the structure of the civil-law obligations (art. 509 of the Civil Code of Ukraine), which is now usually regarded as a relationship. The object of study is the problem of studying the elements of contractual relations retail sale. The aim of the work is to determine what the elements of the contractual relationship retail sale are. Methodological basis of the publication constitute special techniques that are used in legal research. They are comparative and legal, formal and juridical, system, etc. The main results of the paper are examination of peculiarities the elements of the contractual relationship retail sale as elements of its contractual obligations. The contractual obligation is analyzed in the context of Art. 509 of the Civil Code of Ukraine, which, unlike Art. 151 of the Civil Code of the Ukrainian SSR considered it as a legal relationship with his characteristic elements – subject, object and content. The branch of the article’s results implementation is civil and legal, contractual relations in the sphere retail purchase and sale. The practical value of the paper is providing recommendations for improving normative and legal regulation of contractual relations in retail purchase and sale. In the conclusions author argues that the contractual relationship retail sale have the same elements that are inherent to any other civil legal relations – object, subject and content.

Рассмотрены элементы договорных отношений розничной купли-продажи. Указано, что субъектами таких отношений на стороне продавцов товаров могут быть как физические лица – предприниматели, так и юридические лица, имеющие право заниматься бизнесом в сфере розничной торговли. Объектом этих отношений определено поведение (действия) их сторон по поводу передачи права собственности на имущество – товары, которые обычно предназначаются для личного, домашнего или иного использования, не связанного с предпринимательской деятельностью. Содержанием указанных отношений являются субъективные права и обязанности как мера возможного или необходимого поведения сторон таких правоотношений.
Elements of contractual relationship retail sale
Элементы договорных отношений розничной купли-продажи
Keywords: цивільні правовідносини; договірні відносини; елементи договірних відносин; договір роздрібної купівлі-продажу; зобов’язання; суб’єкти; об’єкти; civil relations; contractual relations; elements of contractual relations; contract of retail purchase; obligation; person; objects; гражданские правоотношения; договорные отношения; элементы договорных отношений; договор розничной купли-продажи; обязательство; субъекты; объекты